ANALISIS DESAIN PESAN DAN MATERI PEMBELAJARAN BAHASA ARAB DALAM BUKU AJAR DURUUS AL MUFRADAAT WA AL MUHAADATSAAT AL âARABIYAH - Mukroji, Mukroji (Kelompok Kajian Pendidikan Ikatan Alumni IAIN Purwokerto, 2013)
STAIN Purwokerto has target of Arabic learning on campus, thestudents can talk and communicate with fluent Arabic and actively correct . This target would be difficult to achieve if not supported by the mastery of vocabulary and conversation. Therefore , the book